Hong Kong Higher Education and the 2020 Outbreak: We’ve Been Here Before - Holliday, Ian; Postiglione, Gerard (International Higher Education, 2020)
Universities around the world responded to COVID-19 in different ways. Hong Kong, located close to the origin, was fast to react. Teaching and learning quickly migrated online and universities engaged with challenges in maintaining the quality of instructional delivery. Alongside inevitable downsides generated by real-time re-engineering of higher education, unexpected upsides were also registered. Drawing out the lessons from this most unusual semester will be a key task when campuses are again able to function properly.